The Growth of Palliative Practice and End of Life Care in an Academic Teaching Intensive Care Unit. (October 2022) - King, Daniel; Schockett, Erica; Rizvi, Ghazi; Fischer, Daniel; Amdur, Richard; Benjenk, Ivy; Yamane, David; DelPrete, Benjamin; Davison, Danielle; Seneff, Michael
Objective: Dying in the intensive care unit (ICU) has changed over the last twenty years due to increased utilization of palliative care. We sought to examine how palliative medicine (PM) integration into critical care medicine has changed outcomes in end of life including the utilization of do not resuscitate (no cardiopulmonary resuscitation but continue treatment) and comfort care orders (No resuscitation, only comfort medication).Design: Retrospective observational review of critical care patients who died during admission between two decades, 2008 to 09 and 2018 to 19.Setting: Single urban tertiary care academic medical center in Washington, D.C.Patients: Adult patients who were treated in any ICU during the admission which they died. Interventions and Measurements: We sought to measure PM involvement across the two decades and its association with end of life care including do not resuscitate (DNR) and comfort care (CC) orders.Main Results: 571 cases were analyzed. Mean age was 65 ± 15, 46% were female. In univariate analysis significantly more patients received PM in 2018 to 19 (40% vs. 27%, p = .002). DNR status increased significantly over time (74% to 84%, p = .002) and was significantly more common in patients who were receiving PM (96% vs. 72%, p < 0.001). CC also increased over time (56% to 70%, p = <0.001), and was more common in PM patients (87% vs. 53%, p < 0.001). Death in the ICU decreased significantly over time (94% to 86%, p = .002) and was significantly lower in PM patients (76% vs. 96%, p < 0.001). The adjusted odds of getting CC for those receiving versus those not receiving PM were 14.51 (5.49-38.36, p < 0.001) in 2008 to 09 versus 3.89 (2.27-6.68, p < 0.001) in 2018 to 19.Conclusion: PM involvement increased significantly across a decade in our ICU and was significantly associated with incidence of DNR and CC orders as well as the decreased incidence of dying in the ICU. The increase in DNR and CC orders independent of PM over the past decade reflect intensivists delivering PM services.